Drinking Water Minerals and Mineral Balance : Importance, Health Significance, Safety Precautions - Rosborg, Ingegerd (Springer International Publishing : Imprint: Springer, 2015)
The various safety organizations working on drinking water all warn about unhealthy constituents, as well as elements that can cause corrosion or scaling on pipes and installations. However, drinking water may also provide a substantial portion of the daily mineral intake, especially for the elderly and children, or those at risk of deficiencies due to unhealthy eating habits or starvation. Thus, a holistic approach to drinking water is presented in this book and the scope is extended from standards for undesirable substances to the basic mineral composition of water, examining 22 nutrient elements and ions and 21 toxic substances. The function of the nutrients in the body, symptoms of deficiency and overload, and advantages of the minerals from drinking water are presented, as well as symptoms of toxic elements from drinking water. The authors also suggest healthy ranges of minerals and mineral ratios for drinking water.  The book offers a valuable resource for the health evaluation of drinking waters, for private well owners, public water producers and safety organizations alike.